A novel framework for analyzing conservation impacts: evaluation, theory, and marine protected areas. Issue 1 (18th July 2017) - Mascia, Michael B.; Fox, Helen E.; Glew, Louise; Ahmadia, Gabby N.; Agrawal, Arun; Barnes, Megan; Basurto, Xavier; Craigie, Ian; Darling, Emily; Geldmann, Jonas; Gill, David; Holst Rice, Susie; et al.
Abstract : Environmental conservation initiatives, including marine protected areas (MPAs), have proliferated in recent decades. Designed to conserve marine biodiversity, many MPAs also seek to foster sustainable development. As is the case for many other environmental policies and programs, the impacts of MPAs are poorly understood. Social–ecological systems, impact evaluation, and common‐pool resource governance are three complementary scientific frameworks for documenting and explaining the ecological and social impacts of conservation interventions. We review key components of these three frameworks and their implications for the study of conservation policy, program, and project outcomes. Using MPAs as an illustrative example, we then draw upon these three frameworks to describe an integrated approach for rigorous empirical documentation and causal explanation of conservation impacts. This integrated three‐framework approach for impact evaluation of governance in social–ecological systems (3FIGS ) accounts for alternative explanations, builds upon and advances social theory, and provides novel policy insights in ways that no single approach affords. Despite the inherent complexity of social–ecological systems and the difficulty of causal inference, the 3FIGS approach can dramatically advance our understanding of, and the evidentiary basis for, effective MPAs and other conservation initiatives.